Nilai-Nllai Pendidikan Dalam Pelaksanaan Zakat - Ratih Kumalasari; Puja Hayati; Lidya zanti,; Hanifah Hanifah; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2023)
Zakat isdesigned by Allah SWT for the purpose of human benefit as an individual, social welfare and welfare of the wider environment. In the zakat other than a ritual dimensions there are also positive values that will be internalized to individuals who do, people who accept and wider social environment. Muzakki will obtain these educational values if they meet several conditions. First, he performs zakat based on faith and sincerity. Second, carry out zakat according to the guidance, that is to fulfiiI the requirement, to get along and to do the things that are desirable. Third, to live the meaning behind the worship performed. Fourth, dig maqashid al shari'ah from worship to be executed.